Bright spots among the world’s coral reefs - Cinner, Joshua E.; Huchery, Cindy; Macneill, M. Aaron; Graham, Nicholas A.J.; McClanahan, Tim R.; Maina, Joseph; Maire, Eva; Kittinger, John N.; Hicks, Christina C.; Mora, Camilo; Allison, Edward H.; D'Agata, Stephanie; et al. (Nature Publishing Group, 2016)
Ongoing declines in the structure and function of the world’s coral reefs1, 2 require novel approaches to sustain these ecosystems and the millions of people who depend on them3. A presently unexplored approach that draws on theory and practice in human health and rural development4,5 is to systematically identify and learn from he ‘outliers’—places where ecosystems are substantially better (‘bright spots’) or worse (‘dark spots’) than expected, given the environmental conditions and socioeconomic drivers they are exposed to. Here we compile data from more than 2,500 reefs worldwide and develop a Bayesian hierarchical model to generate expectations of how standing stocks of reef fish biomass are related to 18 socioeconomic drivers and environmental conditions. We identify 15 bright spots and 35 dark spots among our global survey of coral reefs, defined as sites that have biomass levels more than two standard deviations from expectations. Importantly, bright spots are not simply comprised of remote areas with low fishing pressure; they include localities where human populations and use of ecosystem resources is high, potentially providing insights into how communities have successfully confronted strong drivers of change. Conversely, dark spots are not necessarily the sites with the lowest absolute biomass and even include some remote, uninhabited locations often considered near pristine. We surveyed local experts about social, institutional, and environmental conditions at these sites to reveal that bright spots are characterized by strong sociocultural institutions such as customary taboos and marine tenure, high levels of local engagement in management, high dependence on marine resources, and beneficial environmental conditions such as deep-water refuges. Alternatively, dark spots are characterized by intensive capture and storage technology and a recent history of environmental shocks. Our results suggest that investments in strengthening fisheries governance, particularly aspects such as participation and property rights, could facilitate innovative conservation actions that help communities defy expectations of global reef degradation.